Pemanfaatan Potensi Wisata Berbasis Sumber Daya Alam Dan Budaya (Studi Kasus Desa Ekowisata Pancoh Yogyakarta) - Puspadewi, Roels Ni Made Sri; Natalia, Dessy (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2023)
Pancoh Ecotourism Village is located in the Yogyakarta Merapi Volcano area. The location of the village which is quite high and cool makes many people develop natural and cultural products to attract tourists. The research objective is to examine the utilization of natural and cultural resources as a tourist attraction. Tourism activities presented to tourists and management of destinations with the concept of Ecotourism. The research method used is descriptive qualitative research with an exploratory approach. Methods of data collection by observation, interviews, and documentation. Investigation of informants using purposive sampling with a total of 10 informants. The data analysis method used is an interactive model consisting of data collection, data reduction, data presentation, and drawing conclusions. The results of this study are natural resources in the form of processing the potential of the natural environment and not making many changes to the actual conditions. The tourist attractions are river crossings, rice field plows, fish ponds, embung, salak gardens, and biogas. Local arts and culture are used as tourism activities such as the Wiwitan Tradition and playing gamelan. Tourists can learn about preserving traditional ceremonies and traditional musical instruments. Local people are involved in all tourism activities. So that people can benefit economically, on the other hand, nature, and culture can still be properly preserved. Pancoh Ecotourism Village Management can be an example of a destination that maximizes the natural and cultural potential of the village.